Written Errors of Kurdish Learners of Persian: A Case ofMahabadi Dialect - fahime ma'refat (Matn/Pizhūhī-i Adabī, 2005)
The present piece of research is an attempt to discover the nature of students' written errors which help learn about the strategies learners employ and better appreciate the leaning hypotheses. More specifically this study aims at finding the what, the frequency, and the origin of errors Kurdish learners of Persian make. Written essays of I 00 students in the fifth grade of a primary school in Mahabad were analyzed. These students errors were of morphological, syntactic and lexico-scmantic types. Interference from LI just one of the sources of errors, others being the interaction between the two languages, and the learning strategies of the learners.